Anomalous photovoltaics in Janus MoSSe monolayers - Chang Liu; Tianyu Liang; Xin Sui; Lena Du; Quanlin Guo; Guodong Xue; Chen Huang; Yilong You; Guangjie Yao; Mengze Zhao; Jianbo Yin; Zhipei Sun; et al. (Nature Communications)
Abstract The anomalous photovoltaic effect (APE) in polar crystals is a promising avenue for overcoming the energy conversion efficiency limits of conventional photoelectric devices utilizing p-n junction architectures. To facilitate effective photocarrier separation and enhance the APE, polar materials need to be thinned down to maximize the depolarization field. Here, we demonstrate Janus MoSSe monolayers (~0.67 nm thick) with strong spontaneous photocurrent generation. A photoresponsivity up to 3 mA/W, with ~ 1% external quantum efficiency and ultrafast photoresponse (~50 ps) were observed in the MoSSe device. Moreover, unlike conventional 2D materials that require careful twist alignment, the photovoltage can be further scaled up by simply stacking the MoSSe layers without the need for specific control on interlayer twist angles. Our work paves the way for the development of high-performance, flexible, and compact photovoltaics and optoelectronics with atomically engineered Janus polar materials.